Associations between dairy farm performance indicators and culling rates under policy-driven herd size constraints - Kulkarni, Pranav Shrikant; Mourits, Monique; Nielen, Mirjam; Steeneveld, Wilma (Frontiers in Veterinary Science, 2023)
The aim of this study was to study cross-sectional associations between performance of dairy farms and their corresponding culling proportions under the herd size constraint as imposed in 2018 by the new phosphate regulation in the Netherlands. To this end, production data from 10,540 Dutch dairy farms were analyzed to capture the inflow and outflow of both primiparous and multiparous cows. Farm performance was measured by 10 indicators structured in four areas of longevity, production, reproduction, and udder health. Farm culling proportions were represented by the overall culling (OC) and the number of culled primiparous cows in relation to i) total number of producing cows (PC), ii) number of producing primiparous cows (PPC) and iii) number of culled producing cows (POC). Spearman’s rank correlation and weighted logistic regression were adopted to study associations. In 2018, on average, 28% of producing cows were culled (OC). The number of primiparous cows culled represented 4.5% of the total number of producing cows (PC) and mean proportion of culled primiparous cows was 18.8% in total number of producing primiparous cows (PPC) and of the total number of producing culled cows, 15% were primiparous (POC). However, the variance around the mean, and among individual farms, was high (SD 4%-15% for all four culling proportions). Results from the rank correlation showed very low rank conformity (<12%) between the performance areas of production, reproduction, and udder health to the culling proportions. Results from the logistic regression showed that higher farm levels of production and higher percentage of cows with poor udder health were associated with more overall culling but with less primiparous culling. For reproduction indicators the associations were in similar direction for overall and primiparous culling. However, except for the average age of culled animals, the odds ratios for indicators were close to 1 (range: 0.92-1.07 and 0.68-1.07 for OC and PPC, respectively) indicating only weak associations to culling proportions. In conclusion, although the introduction of phosphate regulation resulted in an increased outflow of cattle, corresponding culling proportions were not associated with the level of farm performance measured in production, reproduction, or udder health areas.